2022
DOI: 10.1155/2022/5117986
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] The Performance Appraisal System of Country Well‐Facilitated Farmland Based on AHP‐Object Metatopological Model

Abstract: Performance appraisal of well-facilitated farmland projects has positive significance for promoting the development of modern agriculture in rural areas and carrying out rural revitalization. Based on the AHP-object metatopological model, a well-facilitated farmland project performance appraisal system is proposed to analyze the county performance of well-facilitated farmland construction. In this study, Fangcheng County, Henan Province, is selected as the research sample area and evaluated by applying the est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…In addition, the research found that employee bias has a significant and negative impact on performance appraisal method. The findings of current research are in line with the previous researches (Haralayya, 2022;Meng & Zhang, 2022;Outila & Fey, 2022;Rana et al, 2022;Rubin et al, 2022;Wang et al, 2022). The primary intention behind writing this paper was to study connections that might be made between personal bias and performance rating systems.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In addition, the research found that employee bias has a significant and negative impact on performance appraisal method. The findings of current research are in line with the previous researches (Haralayya, 2022;Meng & Zhang, 2022;Outila & Fey, 2022;Rana et al, 2022;Rubin et al, 2022;Wang et al, 2022). The primary intention behind writing this paper was to study connections that might be made between personal bias and performance rating systems.…”
Section: Discussionsupporting
confidence: 88%
“…Raters describe enduring severe discomfort when doing so. Personal prejudice may originate from a variety of factors, including information learned from colleagues, philosophical and religious convictions, as well as community and family history (Wang et al, 2022). So, it is vital to develop an assessment technique that is inclusive and centered upon the culture, operational structures, and priorities (Buckingham & Goodall, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The research on HSFC has mainly focused on the suitability of HSFC [13][14][15], the benefit evaluation of HSFC [7,[16][17][18], the peasants' participation of HSFC [3,[19][20][21][22][23], the realistic challenges of HSFC [24,25], and the development path of the HSFC [5,6,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%